ACUTE ACHILLES TENDON RUPTURE IN A PROFESSIONAL SOCCER ATHLETE: A CASE REPORT - da Cunha, Luisa Veras Cordeiro; Andraus, Yunen Mikhael; de Oliveira Carmo Borges , Gustavo Henrique; Nascimento Camapum, Mateus; Yokota Guedes, Rafaella; Harumi de Castro Shimazak, Karine; Lopes Pena de Sousa , Rafael (CIPEEX, 2022)
THE CALCANEAL TENDON, OR €ŒACHILLES TENDON€, IS THE STRONGEST IN THE HUMAN BODY, WITH AN ESSENTIAL ROLE IN GAIT. ITS RUPTURE IS MORE FREQUENT IN THE SPORTS AREA DUE TO HIGH ENERGY IMPACTS, MAINLY IN INADEQUATE OR AMATEUR TRAINING SESSIONS. THUS, THIS IS A REPORT OF A CASE OF A TOTAL RUPTURE OF THE "ACHILLES TENDON" FROM A PROFESSIONAL SOCCER PLAYER TREATED IN GOINIA, GOIS (BRAZIL). THE PATIENT INTEGRALLY BROKE THE TENDON ON FIELD DUE TO VIOLENT FOOT DORSIFLEXION, PURELY FROM THE HIGH ENERGY IMPACT OF THE ANKLE ON THE FIELD. BASED ON THE FAST SPIN ECO MAGNETIC RESONANCE IMAGING SCAN - THAT SHOWED A TOTAL ACHILLES TENDON RUPTURE -, THE PATIENT WAS SURGICALLY TREATED USING THE KRACKOW SUTURE TECHNIQUE UNITED WITH SHORT FIBULAR REINFORCEMENT. AFTER SURGERY AND MANAGEMENT OF PAIN AND EDEMA, THE CALCANEAL STRENGTHENING WAS PRIORITIZED, WITHOUT COMPLICATIONS AND WITH GRADUAL NEUROMUSCULAR POSITIVE RESPONSE TO EXERCISE AND VARIOUS STIMULI, WHICH LEAD HIM TO A FAST RETURN ON TRAINING. EVEN THOUGH IT IS AN UNUSUAL RUPTURE FOR PROFESSIONAL ATHLETES, IT HAPPENED DUE TO REPETITIVE MICROTRAUMAS COMBINED WITH RISK FACTORS, WHICH CAUSED FIBER DEGENERATION AND WEAKENED THE MUSCULAR STRUCTURES. THEREFORE, THESE FINDINGS HAVE SIGNIFICANT CLINICAL IMPORTANCE THAT WARRANTS SPECIAL ATTENTION AMONG CLINICIANS. NEVERTHELESS, THIS AREA SHOULD BE MORE STUDIED SINCE IT’S STILL A CHALLENGE FOR PROFESSIONAL ATHLETES SINCE ITS MECHANISMS ARE YET TO BE KNOWN AND IT CAN SEVERELY IMPACT THEIR PERSONAL AND PROFESSIONAL LIFE.